Immune Defenses of a Beneficial Pest: The Mealworm Beetle, Tenebrio molitor - Aurélien Vigneron; Charly Jehan; Thierry Rigaud; Yannick Moret (Frontiers in Physiology, 2019)
The mealworm beetle, Tenebrio molitor, is currently considered as a pest when infesting stored grains or grain products. However, mealworms are now being promoted as a beneficial insect because their high nutrient content makes them a viable food source and because they are capable of degrading polystyrene and plastic waste. These attributes make T. molitor attractive for mass rearing, which may promote disease transmission within the insect colonies. Disease resistance is of paramount importance for both the control and the culture of mealworms, and several biotic and abiotic environmental factors affect the success of their anti-parasitic defenses, both positively and negatively. After providing a detailed description of T. molitor’s anti-parasitic defenses, we review the main biotic and abiotic environmental factors that alter their presentation, and we discuss their implications for the purpose of controlling the development and health of this insect.